A Review Articles: Pantoea agglomerans in UTI- It is Bacteria Caused Urinary Tract Infection and Genomic Analysis related with Bacterial Resistance - Hammed, Zainab Noori; Taha, Abdullah M.; Alabdali, Tareq Abdulrazzaq (Journal for Research in Applied Sciences and Biotechnology, 2023)
Pantoea Spp. is a plant bacteria that has been identified as an emerging pathogen in humans related with outbreaks and many clinical infections. It is referred to as a "mystery bacterium of evil and good" since it may cause both bad and good. With the proposed investigation, the researchers hope to uncover a significant risk component that is connected with reoccurring urinary tract infections (UTI). They also hope to identify bacterial reasons and antibiotic susceptibility profiles that can be used to lower the threat of reinfection and prevent complications associated with recurrent UTI. In the existence of risk variables, the likelihood of developing a UTI increases; also, a correct susceptibility pattern increases the likelihood of achieving therapeutic effectiveness and preventing illness complications. Because of its capacity to infect immunocompromised persons and produce severe illness as a consequence of its multi - drug resistance, Pantoeasppregard is considered to be a dangerous opportunistic pathogen. In this paper we are going to focus on related bacteria, pathogenicity, resistance genes, classification.